Nintedanib plus docetaxel as second-line therapy in patients with non-small-cell lung cancer: a network meta-analysis. (February 2015) - Popat, Sanjay; Mellemgaard, Anders; Fahrbach, Kyle; Martin, Alison; Rizzo, Maria; Kaiser, Rolf; Griebsch, Ingolf; Reck, Martin
ABSTRACT : Background: Nintedanib plus docetaxel has proven an overall survival benefit over docetaxel monotherapy in second-line treatment of non-small-cell lung cancer of adenocarcinoma histology in the LUME-Lung 1 pivotal trial. No published trials have previously compared nintedanib plus docetaxel with agents – other than docetaxel – that are approved second-line treatments for non-small-cell lung cancer.Methods: The relative efficacy of nintedanib plus docetaxel versus second-line agents was evaluated by conducting a network meta-analysis of progression-free survival and overall survival.Results: Nine suitable studies were identified. The estimated probability of nintedanib plus docetaxel being the best treatment with regard to overall survival was 70% (versus 16% for pemetrexed, 10% for docetaxel and 3% for erlotinib). Results for progression-free survival were similar.Conclusion: In patients with advanced non-small-cell lung cancer of adenocarcinoma histology, results suggest that nintedanib plus docetaxel offers clinical benefit compared with docetaxel alone, when used as second-line treatment, and suggests that this combination may also add clinical benefit compared with erlotinib in this patient group.